2017
DOI: 10.2147/hiv.s121021
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among adult HIV patients in Ethiopia: a hospital-based cross-sectional study

Abstract: BackgroundAnemia is a major public health problem in HIV patients around the world. It has a negative effect on the quality of life of HIV patients and progression of the HIV disease. In the sub-Saharan African setting, including Ethiopia where both HIV infection and under-nutrition are expected to be high, there is a paucity of data on the matter. This study was aimed to reveal the magnitude and factors associated with anemia among adult HIV patients in Debre-Tabor Hospital, northwest Ethiopia.MethodsA hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
40
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 12 publications
16
40
10
Order By: Relevance
“…In this study, the overall prevalence of anemia at baseline was found to be 59.0% (24.6% mild, 28.2% moderate and 6.2% severe anemia) which almost exactly in line to a study conducted across Europe where the target groups HIV patients of HAART naïve [29]. The overall prevalence of anemia in the current study was higher than other different studies that ranges from 18.9% in Uganda to 49.6% in Indonesia [25][26][27][28][30][31][32][33][34]. To the contrary, the baseline prevalence was lower than other studies conducted among ART Naïve HIV or TB patients in Ghana, Nigeria and Gambia that had been reported 63.0%, 69.2% and 67%, respectively [11,35,36].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the overall prevalence of anemia at baseline was found to be 59.0% (24.6% mild, 28.2% moderate and 6.2% severe anemia) which almost exactly in line to a study conducted across Europe where the target groups HIV patients of HAART naïve [29]. The overall prevalence of anemia in the current study was higher than other different studies that ranges from 18.9% in Uganda to 49.6% in Indonesia [25][26][27][28][30][31][32][33][34]. To the contrary, the baseline prevalence was lower than other studies conducted among ART Naïve HIV or TB patients in Ghana, Nigeria and Gambia that had been reported 63.0%, 69.2% and 67%, respectively [11,35,36].…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, participants were ascertained their active TB and HIV co-infection status by reviewing ART logbook and patient medical charts. We used the single population proportion formula to estimate the minimum sample size considering the following underlining assumptions -95% confidence level, 5% acceptable level of precision (margin of error), and overall prevalence of anemia (23%) among HIV patients irrespective their ART conducted in Debre-tabor, Ethiopia which is [28].…”
Section: Sample Size Determination and Sampling Proportionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Globally, anemia prevalence in HIV patients who received ART treatment is 23-50%. 32 This study found anemia prevalence of 29,4% in HIV patients who were treated with AZT. This prevalence is consistent with a research result in South West Ethiopia, which was 23,1%.…”
Section: Resultsmentioning
confidence: 62%
“…Anemia can happen each year due to HIV infection, and the degree of anemia is related to the progressivity of the disease. 32 The pathophysiology of anemia in HIV infection is an important factor in disease management, as well as prevention in morbidity and mortality. 7 Prevalence of anemia is around 11,7-92,0%, depending on HIV stadium, sex, age, pregnancy status, and whether or not an opportunistic infection is present.…”
Section: Resultsmentioning
confidence: 99%